Contributions to non-conventional biometric systems : improvements on the fingerprint, facial and handwriting recognition approach - Zaghetto, Cauê (2021)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.